1995
DOI: 10.1002/ps.2780450110
|View full text |Cite
|
Sign up to set email alerts
|

Phloem translocation of pyridinecarboxylic acids and related imidazolinone herbicides in Ricinus communis

Abstract: The movement of [14C]pyridinecarboxylic acids was investigated in the castor bean plant Ricinus communis L. after application by petiole injection. The three isomeric unsubstituted acids appeared in similar concentrations in phloem sap taken from the upper main stem over a period of 6 h after application, but nicotinic acid occurred at higher concentrations than its isomers in phloem sap from the lower stem indicating better retention in the phloem sieve tubes. After 24 h, nicotinic acid had accumulated to a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The degradation of imidacloprid in plants has been described previously, and one of the metabolites found was 6‐chloronicotinic acid, 6‐CNA, exactly matching the physico‐chemical criteria mentioned above 16. 27 Its basipetal mobility had already been reported by others 28. Taking all these aspects into consideration, it is obvious that, 7 days after foliar application of [ 14 C]imidacloprid, the c 5% of radiolabel translocated basipetally was either 6‐CNA or other degradation products with similar properties.…”
Section: Discussionmentioning
confidence: 63%
“…The degradation of imidacloprid in plants has been described previously, and one of the metabolites found was 6‐chloronicotinic acid, 6‐CNA, exactly matching the physico‐chemical criteria mentioned above 16. 27 Its basipetal mobility had already been reported by others 28. Taking all these aspects into consideration, it is obvious that, 7 days after foliar application of [ 14 C]imidacloprid, the c 5% of radiolabel translocated basipetally was either 6‐CNA or other degradation products with similar properties.…”
Section: Discussionmentioning
confidence: 63%
“…Although the same amount of imazamox was present for each pH soil at each sampling time (discussed above), the imazamox present was more bioavailable at pH < 6 than at pH > 6, as evidenced by greater effects on the susceptible oilseed rape. Chamberlain et al . (1995) have shown that, at low pH in liquid culture systems, the undissociated form of the chemical is taken up more efficiently compared with high‐pH soils in which more anion is present.…”
Section: Resultsmentioning
confidence: 99%
“…Although the same amount of imazamox was present for each pH soil at each sampling time (discussed above), the imazamox present was more bioavailable at pH < 6 than at pH > 6, as evidenced by greater effects on the susceptible oilseed rape. Chamberlain et al (1995) have shown that, at low pH in liquid culture systems, the undissociated form of the chemical is taken up more efficiently compared with high-pH soils in which more anion is present. Increased injury in low-pH soils may result from increased desorption of the chemical from the soil colloid making imazamox more bioavailable to the plant along with more efficient uptake and translocation of the undissociated acid form.…”
Section: Field and Greenhousementioning
confidence: 99%
“…However, some of its metabolites meet the physical-chemical conditions to be basipetally translocated, as for example 6-chloronicotinic acid. As a result, this compound or others with the same characteristics can be found in plant parts different from the site of application (Chamberlain et al 1995 ).…”
Section: Environmental Fate and Exposure In Plantsmentioning
confidence: 99%